The Effect of Starfruit Juice to Reduce The Blood Pressure In Elderly Patients - Farida, Endhar Arifathul; Budi, Ilham Setyo; Jamaludin, Jamaludin (South East Asia Nursing Research, 2020)
Hypertension is classified as a disease that is often called the Silent Killer. Hypertension can attack various ages, including the elderly. Hypertension in the long term will cause various complications. In the Treatment of hypertension, many natural plants can be consumed, one of which is star fruit. Sweet starfruit juice is very useful for lowering blood pressure because of its fibre, potassium, phosphorus and vitamin C content.  This study was to determine the effect of starfruit juice on lowering blood pressure in elderly people with hypertension at the integrated service centre in the working area of Rejosari Dawe Kudus Public Health Center. This study used a Quasy experiment method with a pre-test-post-test research design with a control group. A sample of 20 people, divided into two groups, namely 10 people in the experimental group and 10 people in the control group.  The results of the independent t-test, the results of the posttest systolic blood pressure p-value = 0.004, while the diastolic blood pressure posttest p-value = 0.014, so it can be seen that the p-value <0.05, then H0 is rejected and Ha is accepted.  In this study, it can be concluded that there is an effect of giving star fruit juice on reducing blood pressure in elderly people with hypertension at the integrated service centre in the working area of the Rejosari Dawe Kudus Community Health Center.